Incidence of Deep Sternal Wound Infection Is Not Reduced with Autologous Platelet Rich Plasma in High-Risk Cardiac Surgery Patients - Dörge, Hilmar; Sellin, Christian; Bury, Maike-Corinna; Drescher, Andreas; Seipelt, Ralph; Grossmann, Marius; Danner, Bernhard C.; Schoendube, Friedrich A. (The Thoracic and Cardiovascular Surgeon, 2013)
Background Deep sternal wound infections (DSWI) remain a devastating complication in cardiac surgery applying full sternotomy. As the risk profile in cardiac surgery changed toward an older and sicker population, the incidence of DSWI increases. Platelet rich plasma (PRP) holds promise in tissue regeneration with respect to bone regeneration, reduction of bleeding, and accelerated wound healing. The effect of PRP on DSWI was investigated in high-risk patients undergoing cardiac surgery with full sternotomy.Methods 196 consecutive patients at risk of DSWI were randomized to application of autologous PRP before sternal wiring (n = 97) or control (n = 99). All patients underwent cardiac surgery on cardiopulmonary bypass with cardioplegic cardiac arrest. Endpoint was occurrence of DSWI requiring revision surgery.Results Demographic, intraoperative, and perioperative variables as well as risk factors were comparable between groups. Incidence of DSWI was not different between the PRP-group and the control-group (6/97 (6.2%) vs. 3/99 (3.0%); n.s.).Conclusions Local application of autologous PRP in cardiac surgery patients with full sternotomy at high risk for sternal complications did not reduce the incidence of DSWI.
Keywords: sternum; wound infection; wound healing; surgery complications